Applied methods for 3D modeling of radio engineering devices - Ivanova, Yoana (Yearbook Telecommunications, 2024)
The aim of the paper is to present applied methods for engineering 3D modeling of pyramidal and conical horn antennas, which can contribute to the implementation of experimental research, both in a simulation and in a physical environment. The practical results presented at each step of the model building process are represented by screenshots of the work screen showing the used toolbars from the Autodesk 123D Design software menu. This is done with a view to improving the quality of training in areas related to the study of radio engineering devices, such as telecommunications engineering and aerospace engineering, in which the design and manufacture of various types of antennas help to conduct independent empirical research by the trainees with the help of measuring equipment.